Democratism - Agné, H. (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This insightful and timely book introduces an explanatory theory for surveying global and international politics. Describing the nature and effects of democracy beyond the state, Hans Agné explores peace and conflict, migration politics, resource distribution, regime effectiveness, foreign policy and posthuman politics through the lens of democratism to both supplement and challenge established research paradigms.